Selective impairment of race perception after bilateral damage in the fusiform and parahippocampal gyri. Issue 3 (29th May 2013) - Koyama, Shinichi; Midorikawa, Akira; Suzuki, Atsunobu; Hibino, Haruo; Sugimoto, Azusa; Futamura, Akinori; Kawamura, Mitsuru
Abstract Aim Although a previous functional magnetic resonance imaging study showed that the fusiform and parahippocampal gyri respond differentially to faces of the same versus different races, it is not clear whether the cortical regions are involved in perception of race. We examined whether two brain‐damaged patients with bilateral fusiform and parahippocampal lesions were able to perceive race. We also examined whether perception of race depended on perception of facial morphology, such as convex and concave surfaces. Methods One patient (patient S) had a focal lesion in the fusiform and parahippocampal gyri, and showed no signs of prosopagnosia. The other patient (patient O) had more extensive lesions and did show prosopagnosia. The patients and nine normal controls participated in a psychophysical race classification task using grayscale pictures and luminance‐reversed pictures. Results In patient S, whose lesion was limited to the fusiform and parahippocampal gyri, the perception of race was selectively impaired. In patient O, who had more extensive lesions, race perception was also impaired. Furthermore, their race perception was especially impaired when the facial images were presented in reversed luminance. Conclusion The present study suggests that the fusiform and parahippocampal gyri are involved in perception of race and that perception of facial surface is involved in distinguishing between races.